SORIANO, NIEVES: ’VIAJEROS ROMANTICOS A ORIENTE: DELACROIX, FLAUBERT, NERVAL’ - Cervera Salinas, Vicente (Cartaphilus, 2009)
VIAJEROS ROMANTICOS A ORIENTE: DELACROIX, FLAUBERT, NERVAL Nieves Soriano Nieto Editum, 2009.